2020
DOI: 10.3390/biom10121598
|View full text |Cite
|
Sign up to set email alerts
|

TORC2-Dependent Ypk1-Mediated Phosphorylation of Lam2/Ltc4 Disrupts Its Association with the β-Propeller Protein Laf1 at Endoplasmic Reticulum-Plasma Membrane Contact Sites in the Yeast Saccharomyces cerevisiae

Abstract: Membrane-tethered sterol-binding Lam/Ltc proteins localize at junctions between the endoplasmic reticulum (ER) membrane and other organelles. Two of the six family members—Lam2/Ltc4 (initially Ysp2) and paralog Lam4/Ltc3—localize to ER-plasma membrane (PM) contact sites (CSs) and mediate retrograde ergosterol transport from the PM to the ER. Our prior work demonstrated that Lam2 and Lam4 are substrates of TORC2-regulated protein kinase Ypk1, that Ypk1-mediated phosphorylation inhibits their function in retrogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
(73 reference statements)
2
10
0
Order By: Relevance
“…Given our findings [ 211 ] that Ypk1-mediated phosphorylation of Lam2 and Lam4 inhibits their function in retrograde sterol transport, we sought to understand the mechanism of this negative regulation. We found [ 222 ], in agreement with a prior study [ 58 ] that, at ER-plasma membrane contact sites, Lam2 and Lam4 associate with two paralogous β-propeller (WD40 repeat) proteins Laf1/Ymr102c and Dgr2/Ykl121w, one of which was detected as a sterol-binding protein [ 223 ]. Using fluorescent tags, we showed that Lam2 and Lam4 remain at ER-plasma membrane contact sites when Laf1 and Dgr2 are absent, whereas neither Laf1 nor Dgr2 remain at ER-plasma membrane contact sites when Lam2 and Lam4 are absent [ 222 ].…”
Section: Functions Of Ypk1supporting
confidence: 91%
See 1 more Smart Citation
“…Given our findings [ 211 ] that Ypk1-mediated phosphorylation of Lam2 and Lam4 inhibits their function in retrograde sterol transport, we sought to understand the mechanism of this negative regulation. We found [ 222 ], in agreement with a prior study [ 58 ] that, at ER-plasma membrane contact sites, Lam2 and Lam4 associate with two paralogous β-propeller (WD40 repeat) proteins Laf1/Ymr102c and Dgr2/Ykl121w, one of which was detected as a sterol-binding protein [ 223 ]. Using fluorescent tags, we showed that Lam2 and Lam4 remain at ER-plasma membrane contact sites when Laf1 and Dgr2 are absent, whereas neither Laf1 nor Dgr2 remain at ER-plasma membrane contact sites when Lam2 and Lam4 are absent [ 222 ].…”
Section: Functions Of Ypk1supporting
confidence: 91%
“…We found [ 222 ], in agreement with a prior study [ 58 ] that, at ER-plasma membrane contact sites, Lam2 and Lam4 associate with two paralogous β-propeller (WD40 repeat) proteins Laf1/Ymr102c and Dgr2/Ykl121w, one of which was detected as a sterol-binding protein [ 223 ]. Using fluorescent tags, we showed that Lam2 and Lam4 remain at ER-plasma membrane contact sites when Laf1 and Dgr2 are absent, whereas neither Laf1 nor Dgr2 remain at ER-plasma membrane contact sites when Lam2 and Lam4 are absent [ 222 ]. Furthermore, loss of Laf1 (but not Dgr2) impeded retrograde ergosterol transport, and a laf1Δ mutation did not exacerbate the transport defect of lam2Δ lam4Δ cells, indicating a shared function.…”
Section: Functions Of Ypk1supporting
confidence: 91%
“…Loss of these four retained tethers reduces the amount of cortically retained ER at anaphase II but does not completely prevent ER retention, suggesting that additional tethers and/or alternative mechanisms ensure cortical ER tethering in this context. In addition to the six defined tethers, other proteins have been observed to localize to ER-PM contact sites, and some have been proposed as active ER-PM tethering proteins ( Petkovic et al, 2014 ; Topolska et al, 2020 ). Study of these additional factors will be important to further interrogate the molecular basis of cortical ER retention during meiosis and its role in ensuring gamete health.…”
Section: Discussionmentioning
confidence: 99%
“…However, deletion of all six tethers eliminates almost all cortical ER even in non-meiotic cells, complicating our ability to assess meiotic cortical ER retention in this genotype. In addition to these six tethers, other proteins have been observed to localize to ER-PM contact sites, and some have been proposed as active ER-PM tethering proteins (Petkovic et al, 2014; Topolska et al, 2020). Study of these additional factors will be important to further interrogate the molecular basis of cortical ER retention during meiosis and its role in ensuring gamete health.…”
Section: Discussionmentioning
confidence: 99%